How Does Emotional Intelligence Affects Teachers’ Contextual Performance? A Path Analysis - Chandrawaty, Chandrawaty; Widodo, Widodo (Jurnal Pendidikan Progresif, 2022)
How Does Emotional Intelligence Affects Teachers’ Contextual Performance? A Path Analysis. Objectives: This study explores the effect of emotional intelligence on interpersonal communication and teachers’ contextual performance, and how interpersonal communication mediating emotional intelligence affects contextual performance. Methods: A questionnaire collected data through the survey methods toward 230 public elementary school teachers in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. Finding: The results show that emotional intelligence had a significant effect on teachers’ contextual performance, directly and indirectly, mediated by interpersonal communication. Conclusion: A new model regarding the effect of emotional intelligence on teachers’ contextual performance, mediated by interpersonal communication, was confirmed. Thus, the researchers and educational practitioners can discuss and adopt a new empirical model to improve teachers’ contextual performance through emotional intelligence and interpersonal communication in the future. Keyword: emotional intelligence, interpersonal communication, contextual performance, teacher.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202222